2020
DOI: 10.1016/j.jclinepi.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Single-reviewer abstract screening missed 13 percent of relevant studies: a crowd-based, randomized controlled trial

Abstract: Objectives: To determine the accuracy of single-reviewer screening in correctly classifying abstracts as relevant or irrelevant for literature reviews. Study Design and Setting: We conducted a crowd-based, parallel-group randomized controlled trial. Using the Cochrane Crowd platform, we randomly assigned eligible participants to 100 abstracts each of a pharmacological or a public health topic. After completing a training exercise, participants screened abstracts online based on predefined inclusion and exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 14 publications
2
88
0
1
Order By: Relevance
“…We also undertook a second scoping review that identified 14 empirical studies that evaluated RR methods, which we mapped to stages of review conduct [23]. The RRMG also led two methodological studies: one that assessed the impact of limiting inclusion criteria solely to English language publications [24] and one that assessed the accuracy of single-reviewer screening vs. dualreviewer screening as part of an online parallel group randomized controlled trial using the Cochrane Crowd platform [25]. Collectively, this work formed the evidentiary base for the subsequent RR methods options survey.…”
Section: Underlying Evidence and Primary Studies For Rr Defining Featmentioning
confidence: 99%
“…We also undertook a second scoping review that identified 14 empirical studies that evaluated RR methods, which we mapped to stages of review conduct [23]. The RRMG also led two methodological studies: one that assessed the impact of limiting inclusion criteria solely to English language publications [24] and one that assessed the accuracy of single-reviewer screening vs. dualreviewer screening as part of an online parallel group randomized controlled trial using the Cochrane Crowd platform [25]. Collectively, this work formed the evidentiary base for the subsequent RR methods options survey.…”
Section: Underlying Evidence and Primary Studies For Rr Defining Featmentioning
confidence: 99%
“… 35 Trade-offs in comprehensiveness and rigour increase the risk of bias with resultant type 1 (false positive) and type 2 (false negative) errors, and reduce the certainty/quality of the review findings. 35 This concept is critical to consider in RRs and particularly for TCIM, as the conclusions of the review are rarely based on the totality of the literature, 36 but instead a limited subset, which is therefore more prone to bias.…”
Section: Reproducibility Transparency and Biasmentioning
confidence: 99%
“…If screening and data extraction are performed by one person, errors might remain undetected. For example, a recently published trial shows that single-reviewer abstract screening misses 13% of relevant studies [25]. Finally, a lack of quality assessment of the included articles may limit the validity of a rapid review as a whole [12,26].…”
Section: Discussionmentioning
confidence: 99%